Modification of Taro Starch with Autoclaving-Cooling Method as a Source of Functional Food - Wiadnyani, A.A. Istri Sri; Permana, I.D.G. Mayun; Widarta, I.W. Rai (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 2 (2017): Scientific Journal of Food Technology, 2017)
Limited functional characteristic of taro starch cause limited application on food product. It is a reason for physical modification of starch with autoclaving-cooling method intended to improve physical, chemical and functional characteristics of taro starch to broaden its usage on food industry and to increase its added value as functional food. In this research, taro starch modification was done with autoclaving-cooling method through modification cycles consisting of without cycle, one cycle, and two cycles. The results indicated that the best treatment is two-cycle autoclaving-cooling modification with swelling power of 8.28 g/g, solubility of 3.77%, amylose of 29.96%, resistant starch of 4.38% and no viscosity peak, but increase in viscosity continuously occur during heating till cooling of 3133.33 cp.